Pengaruh Self Efficacy dan Dukungan Sosial Keluarga terhadap Perencanaan Karier Siswa Kelas XI SMA Negeri 6 Cirebon - Sabila, Iqla Akmala; Saraswati, Sinta (Universitas Mathla'ul Anwar Banten, 2025)
This study aims to determine the effect of self-efficacy and family social support on career planning of class XI students of SMA Negeri 6 Cirebon. Career planning is one of the important aspects in the individual development stage during adolescence. Self-efficacy acts as an internal factor in the form of confidence in students' abilities, while family social support is a motivator for students from the closest social environment. This study uses a quantitative approach with multiple linear regression methods. The subjects of the study were 199 class XI students of a high school in Cirebon City who were selected through random sampling techniques. The instruments in the study used a scale of self-efficacy, family social support and career planning that had been tested for validity and reliability. The results of the analysis showed that self-efficacy and family social support had a simultaneous effect on students' career planning, with a calculated F value of 88.987 and a significance of <0.001. Partially, self-efficacy has a dominant influence with a t count of 10.591 (p <0.001), followed by family social support with a t count of 3.542 (p <0.001). The coefficient of determination (R2) of 0.476 indicates that 47.6% of students' career planning can be influenced by the two independent variables. These results indicate the importance of strengthening students' self-efficacy and collaboration between schools and students' families in supporting the readiness of their future career planning.